A Critical Study on Marketing of Financial Services In Private Sector Banks: Examining Customer Interactions and Services in Private Sector Banks (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A service can be described as the way in which we dealwith our customer each time they have a ‘service encounter’. This encounter isthe direct interaction between the organization and one of its customers andcan occur in one of many ways. For example, a bank customer who wishes to drawmoney from his account can do so in one of many ways. He can go to a branch andrequest the money from a cashier, he can go into the branch and use an ATM, orhe can use an ATM situated in a remote location away from the branch of thebank. Each of these is an interaction with the organization, and the way inwhich the customer is dealt with during that interaction is important to thecustomer and the way he or she feels about the service.